“The Melancholy Bubble”. Emotional dangers in social media - Padilla Castillo, Graciela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Social media can promote stigmatisation, when users share their ideas, opinions, demonstrations and bodies. Stigma creates a “bubble of melancholy”, the original concept of this proposal: they consume publications with similar problems, do not denounce hate, do not ask for help and do not perceive the dangers of the networks. Algorithms do not help and suggest negative and pessimistic content, which keeps them in a sphere of sadness. This article conducts a deontological exploration of the community standards of the social networks Facebook, YouTube, Instagram and TikTok, to find out whether this problem is addressed and if so, how it is combated.